INVASIVE GRASS IN INDONESIA: WHAT HAPPEN UP TO 2012? WITH COMPARISON OTHER INSTITUTION AND GOVERNMENT - alex sumadijaya (BIOTROPIA, 2012)
p { margin-bottom: 0.08in; } Invasive grass with dominant presence in ecosystem is often a neglected flora component. Meanwhile, the term â€œinvasiveâ€ must be standardized, for practical purpose must be considered as urgent matter. Various attempts to compile invasive grass in Indonesia were conducted sporadically by several experts across generations. Scattered data along pile of literatures awaiting to be written in order to produce a comprehensive list of invasive grass. This paper represents the first attempt in drafting the invasive grass list of Indonesia by using literatures.